Implementasi Sensor Magnetic Door Switch Untuk Keamanan Laci Uang Yang Berbasis Internet Of Things(IOT): Studi Kasus Toko Satoya - Ghanis Alnashit Satoya; Danang Haryo Sulaksono (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2021)
Theft is a crime which is an act of taking the property of another person illegally. This is contained in Chapter XXII Articles 362-367 of the Criminal Code. An act of theft exists because it is caused by poverty, ignorance, and economic pressure that tend to make people deviate (theft). Therefore, there is a development of a device with a magnetic sensor that will be installed in a store which can help sellers to be able to provide security in their shop. Researchers made an IoT-based tool for a storage security system using a magnetic door switch sensor. This sensor will be useful for shop owners so that this sensor will be installed in a drawer for storing money or valuables of the shop owner. So when someone is not known to open a drawer that has been installed using a magnetic switch, the alarm will automatically sound and give a notification message to the application that has been connected to the device.